O poder pelo mar: a indústria de construção naval militar no Brasil a partir da política desenvolvimentista de Juscelino Kubitschek (1956-1961) - Amaral, Misael Henrique Silva do (2013)
This work aims to analyze the impacts of the development policy of Juscelino Kubitschek, who through legal devices implanted the shipbuilding industry in Brazil and the impact of this policy on military shipbuilding, and the Navy Yard in Rio de Janeiro (AMRJ) as representative of this process. Brazil is led to a mobilization of development based on industrialization and in this sense it is worth emphasizing three aspects importantes.As JK government measu res in the marine industry and as reflected in the Navy Yard in Rio de Janeiro. Another aspect is the historical moment of the 1950s experiencing the stage of the cold war between the powers Stays States (U.S.) and the Soviet Union (USSR) and it brings suc h developments from military agreements between the U.S. and its allies, with the agreement between Brazil and U.S. inserted in this context. The deployment of military shipbuilding industry in the country in the second half of the fifties in Brazil brough t a significant impact in the military shipbuilding, especially in the 1970s, when the Brazilian Navy regained his ability to design and build modern warships.